In our backyard : how 3 L.A. neighborhoods affect kids' lives - Pebley, Anne R., 1953-; Vaiana, Mary E.; Rand Corporation; W.M. Keck Foundation (Santa Monica, CA : RAND, 2002)
Researchers and specialists in child development have noted a subtle interaction between children's well-being and the neighborhoods in which they grow up. The Focused Study of Children and Neighborhoods (FSCN), on which this book is based, is a survey of three neighborhoods in Los Angeles conducted in 1998. The text is based on data from the 91 families included in that survey and presents highlighted vignettes based on composites of real children in Los Angeles neighborhoods. The authors consider the age of the community's residents, their incomes, and residential turnover in the neighborhood, all of which are thought to be important for children, and draw inferences from the FSCN responses. The next step in the process of discovering how neighborhoods affect children will be a large-scale survey of children living in 65 neighborhoods throughout Los Angeles County, called the Los Angeles Family and Neighborhood Survey (LA FANS).
Includes bibliographical references (p. 36).
Also available on the internet via WWW in PDF format.
Keywords: Child development -- California -- Los Angeles; Children -- California -- Los Angeles -- Social conditions; Community life -- California -- Los Angeles; Neighborhood -- California -- Los Angeles